Air-Mode Photonic Crystal Micro-Ring Resonator With Enhanced Quality Factor for Refractive Index Sensing - Yameng Xu; Shubo Hu; Mei Kong (IEEE Photonics Journal, 2020)
Intense light-matter interaction is critical for enabling high-sensitivity refractive index sensors, high-efficiency light sources, and high-performance nonlinear devices. A bowtie-hole photonic crystal micro-ring resonator is proposed and numerically demonstrated to enhance the light-matter interaction effectively through achieving strong spatial and temporal light confinement, simultaneously. Through engineering the photonic crystal unit cell, the bowtie-hole photonic crystal is proved to possess the ability to localize light with a highly tight spatial confinement. By optimizing the bowtie-hole radius and the bowtie angle, the Q factor of the air mode in the resonator is improved to 1.42 × 105, which denotes an excellent temporal confinement. With the advantages addressed, the refractive index sensing based on the high-Q air mode in the bowtie-hole photonic crystal micro-ring resonator is investigated. For the air mode in the bowtie-hole photonic crystal micro-ring resonator, the Q factor is comparable with that in the reported research, meanwhile the sensing sensitivity has a 2-fold enhancement.